Genetic testing for familial hypercholesterolemia in a Finnish cohort of patients with premature coronary artery disease and elevated LDL-C levels - Jokiniitty, Antti; Eskola, Markku; Metso, Saara; Bogsrud, Martin; Huhtala, Heini; Saarela, Tanja (Frontiers in Cardiovascular Medicine, 2024)
Based on Finnish LDLR-founder variations the prevalence of Familial Hypercholesterolemia (FH) in Finland is estimated to be at least 1:600. Patients with FH have increased risk of premature coronary artery disease (CAD) and thus the prevalence of FH is expected to be higher in this subgroup.To assess the prevalence of monogenic FH in a Finnish cohort of patients with premature CAD and elevated LDL-C levels.Among 28 295 patients undergoing angiography at Heart Hospital at Tampere University Hospital between 2007 and 2017, we identified 162 patients diagnosed with premature CAD (men < 55 years and women < 60 years) and history of high LDL-C (≥ 5 mmol/l) levels without secondary causes of hypercholesterolemia. Clinical probability of FH was estimated, and genetic testing of FH was carried out in 80 patients with informed consent.Of the 80 patients with premature CAD and history of high LDL-C levels, 70% were male, age at diagnosis of CAD for male and female were 48 and 53 years, respectively. Fifty-eight patients (73%) had probable (n=54), or definite (n=4) FH based on DLCN criteria. Pathogenic variant of FH was found in five (6%) patients. Prevalence of the genetically verified FH was 1:16. FH variant was found in 75% of the patients with definite FH.The prevalence of genetically verified FH was 1:16 among patients with premature CAD and elevated LDL-C level, which is 38 times higher than the estimated prevalence of 1:600 in the general Finnish population.